ANALISIS DAMPAK KONVERSI TANAMAN TEH KE TANAMAN KELAPA SAWIT PADA PT. PERKEBUNAN NUSANTARA IV MARJANDI TERHADAP TINGKAT KESEJAHTERAAN MASYARAKAT - Tiodora Siringoringo; Ramli Ramli (Departemen Ekonomi Pembangunan USU, 2014)
The purpose of this study is to analyze the impact of the tea plantation conversion to palmoil plantation at PT Nusantara IV Marjandi toward the level of social welfare. This study uses primary data through questionnaires and interviews to the employees of PTPN IV Marjandi and to the people around PTPN IV Marjandi and secondary data obtained from PT PTPN IV Marjandi. The analytical methods used in this study is Test T - Test and descriptive statistic.The results showed that the conversion have negative impact tothe work chance in the PTPN IV Marjandi,positive impact on the level of labor income because there is a very significant difference between average labor income before and after the conversion of the tea plantation to palmoilplantation, and positive impact on the level of people income because there is a significant difference between the average income of the people before and after tea plantation conversion to palmoil plantations.Keywords :Land Conversion, Tea, Palm Oil, Earnings